KEHIDUPAN KRISTEN ERA REFORMASI - Zuniasa Nazara; Ezra Tari (Institut Agama Kristen Negeri Toraja, 2021)
This study departs from the Christian life of the reform era. Where the Church seems unable to serve amid poverty and political uncertainty. Christianity is challenged to contextualize theology, mission, dialogue, political service in society. The problem of closing the Church was due to the issue of building permits. The author aims in this research is that the Church strives for peace for all people. The approach of this study is a literature study on the thinking and struggles of the Church in society. So the Church does not only take care of the organization and a large amount of money in the church treasury. Nevertheless, the Church is required to care about social problems that occur. Therefore, the Church must apply several principles, namely: first, the Church needs to understand other people's religions. Second, the Church needs to build healthy discussions both between religions and between denominations. Third, the Church prioritizes the mission for the benefit of humanity. Pengkajian ini berangkat dari kehidupan keKristenan era reformasi. Di mana gereja terkesan belum mampu melayani di tengah masalah kemiskinan dan politik yang tidak menentu. Keristenan ditantang untuk mengontektualisasikan teologi, misi, dialog, pelayanan politik di tengah masyarakat. Persoalan penutupan gereja karena persoalan izin mendirikan bangunan (IMB). Tujuan Penulis dalam tulisan ini adalah agar gereja memperjuangkan pedamaian bagi seluruh umat. Pendekatan kajian ini adalah studi literatur terhadap pemikiran dan pergulatan gereja di tengah masyarakat. Jadi gereja tidak hanya mengurus organisasi saja dan banyaknya uang dalam kas gereja. Tetapi gereja dituntut untuk peduli terhadap masalah sosial yang terjadi. Oleh karena itu, gereja harus menerapkan beberapa prinsip yakni: pertama, gereja perlu memahami agama orang lain. kedua, gereja perlu membangun diskusi yang sehat baik antar agama atau antar denominasi. Ketiga, gereja mengutamakan misi bagi kemaslahatan manusia.